Pengaruh Kecepatan Pendinginan Terhadap Perubahan Volume Leburan Polymer Crystalline dan Non-Crystalline - Mohammad Fahrurrozi; Bagus Senowulung dan Moristanto (Faculty of Engineering, Universitas Gadjah Mada, 2003)
AbstractThe study was directed to develop a method to predict the influence of the rate of cooling to the degree of crystallittitv (DOC) and volume change of crystalline polymers. Crystalline polymer melts exhibit volume shrinkage on cooling below melting point due to crystallization. Crystallization and volunrc shrinkage will proceed with varies rate as long as the temperature is above the glass tansition temperatrre. DOC achieved by polymer is not only determined by the inherent crystallinity of the polymer but also influenced by the rate of cooling. Onfast cooling, inherently crystalline polynrer may have zero DOC. This incompletely crystallized polymer will crystallize and experience volume shrinkages on prolong usage at temperatures above glass transition temperature. A mathematical model and a kinetic model of crystallization based of modification of Avrami equation were solved sintultaneously to give temperature and DOC distributions as ftmctions of time for various rote of cooling. Rate of cooling was varied by changing the water hath ternperalure. Labotatory measurement was done to verifu the predicted temperature profile and average degree of crystallinity. The simulated tenxperature profiles as well as average degree of crystallinities give good agreements with experimental results.Keywords: polymer, degree of crystallinity, cooling, melting point, crystallization, volume shrinkage, molding